Creation and cost-evaluation of a student-run podcast in ophthalmology - Ruparelia, Sunil; Nguyen, Anne X; Xu, Haochen; Le, Christopher (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2023)
Implication StatementPodcasts are an increasingly popular medical education modality, especially in surgical fields. However, the cost of developing a high-quality medical education podcast presents a barrier to many content creators. The authors developed the podcast series ‘The Lenspod,’ designed to be a cost-efficient but high-quality education resource in ophthalmology. The REC financial framework has been previously used to estimate the financial costs of technology-based medical education. Using this framework, costs were competitive with other medical education podcasts. It is our hope that similar methodology may be used to create and disseminate future podcasts for medical education.